Autonomic and subjective responsivity to emotional images in people with dissociative seizures. Issue 2 (28th December 2017) - Pick, Susannah; Mellers, John D. C.; Goldstein, Laura H.
Abstract : People with dissociative seizures (DS) report a range of difficulties in emotional functioning and exhibit altered responding to emotional facial expressions in experimental tasks. We extended this research by investigating subjective and autonomic reactivity (ratings of emotional valence, arousal and skin conductance responses [SCRs]) to general emotional images in 39 people with DS relative to 42 healthy control participants, whilst controlling for anxiety, depression, cognitive functioning and, where relevant, medication use. It was predicted that greater subjective negativity and arousal and increased SCRs in response to the affective pictures would be observed in the DS group. The DS group as a whole did not differ from controls in their subjective responses of valence and arousal. However, SCR amplitudes were greater in 'autonomic responders' with DS relative to 'autonomic responders' in the control group. A positive correlation was also observed between SCRs for highly arousing negative pictures and self‐reported ictal autonomic arousal, in DS 'autonomic responders'. In the DS subgroup of autonomic 'non‐responders', differences in subjective responses were observed for some conditions, compared to control 'non‐responders'. The findings indicate unaffected subjective responses to emotional images in people with DS overall. However, within the group of people with DS, there may be subgroups characterized by differences in emotional responding. One subgroup (i.e., 'autonomic responders') exhibit heightened autonomic responses but intact subjective emotional experience, whilst another subgroup (i.e., 'autonomic non‐responders') seem to experience greater subjective negativity and arousal for some emotional stimuli, despite less frequent autonomic reactions. The current results suggest that therapeutic interventions targeting awareness and regulation of physiological arousal and subjective emotional experience could be of value in some people with this disorder.